Studi Literatur: Pendekatan Human Element pada Buku Teks Chemistry Human Activity, Chemical Reactivity Karya Mahaffy dkk Materi Kesetimbangan Asam Basa dalam Larutan - Widia Hizriati; Faizah Qurrata Aini (Universitas Negeri Padang, 2022)
A variety of skills have shaped the teaching and learning of chemistry in the early 21st century. This includes fundamental changes in chemistry such as changes in understanding of how students learn, the application of computer and information technology in studying complex scientific phenomena, and others. Responding to this problem, chemistry education which originally used a